Diagnostic potential of the amniotic fluid cells transcriptome in deciphering mendelian disease: a proof-of-concept - Lee, Mianne; Kwong, Anna K. Y.; Chui, Martin M. C.; Chau, Jeffrey F. T.; Mak, Christopher C. Y.; Au, Sandy L. K.; Lo, Hei Man; Chan, Kelvin Y. K.; Yepez, Vicente A.; Gagneur, Julien; Kan, Anita S. Y.; Chung, Brian H. Y. (npj Genomic Medicine, 2022)
RNA sequencing (RNA-seq) is emerging in genetic diagnoses as it provides functional support for the interpretation of variants of uncertain significance. However, the use of amniotic fluid (AF) cells for RNA-seq has not yet been explored. Here, we examined the expression of clinically relevant genes in AF cells (n = 48) compared with whole blood and fibroblasts. The number of well-expressed genes in AF cells was comparable to that in fibroblasts and much higher than that in blood across different disease categories. We found AF cells RNA-seq feasible and beneficial in prenatal diagnosis (n = 4) as transcriptomic data elucidated the molecular consequence leading to the pathogenicity upgrade of variants in CHD7 and COL1A2 and revising the in silico prediction of a variant in MYRF. AF cells RNA-seq could become a reasonable choice for postnatal patients with advantages over fibroblasts and blood as it prevents invasive procedures.
CRIS-Team Scopus Importer:2023-03-11